Molecular imprinted polymer films on RFID tags: a first step towards disposable packaging sensors. Issue 5 (12th February 2013) - Croux, Dieter; Vangerven, Tim; Broeders, Jeroen; Boutsen, Jan; Peeters, Marloes; Duchateau, Stijn; Cleij, Thomas; Deferme, Wim; Wagner, Patrick; Thoelen, Ronald; De Ceuninck, Ward
Abstract Molecular imprinted polymer (MIP) sensors offer a high potential in the development of cheap small‐scale disposable biomimetic sensors. Molecular imprinting leads to the formation of inert polymer particles with nanocavities, which can exhibit similar selectivity and specificity to target molecules as antibodies or enzymes. These sensors open up many possible applications in the field of mass‐market consumer products such as food packaging sensors. One such application is the detection of histamine in spoiled fish, which causes scombroid poisoning, a common seafood poisoning. This contribution provides one possible solution for easing the use of these sensors in field applications. A screen‐printed short‐range wireless MIP‐based biosensor based upon passive radio frequency identification (RFID) tags was developed as a proof of principle. Histamine molecules binding to an MIP recognition layer induce a dielectric change in the sensor capacitance, resulting in a resonance frequency shift that is transmitted by inductive coupling. This wireless sensor is capable of detecting histamine concentrations as low as 50 nM at a range of a few centimeters.